PRODUCTION AND OPTIMIZATION OF XYLANASE FROM ESTUARINE BACILLUS CEREUS - KRISHNAVENI.M; KOWSALYA.R (International Journal of Pharma and Bio Sciences, 2011)
Xylan is the most abundant non cellulosic material present in both hardwoods and annual plants, and accounts for 20-35% of the total dry weight in tropical plant biomass. In this study xylanase producing Bacillus cereus colonies from vellar estuarine soil sample was isolated and its phenotypic characteristics were also identified. The optimization of pH, temperature, salinity and substrate concentration were characterized by different assay conditions. Purification of xylanase was carried out by ammonium sulphate precipitation method and determination of its molecular weight by SDS-PAGE. The water and sediment sample collected in vellar area was found to harbor respectively 1.0×106 CFU/ml and 1.25×107CFU/g xylanase producing strains. The optimum pH, temperature, salinity and substrate concentration were as follows 8.0,30ºc, 0.9% and 2.5%. The molecular weight was 22KDa and 24KDa as determined by SDS-PAGE. This study proved that the vellar estuary is abundant in xylanase producing bacteria.